Calculations of Performance Losses for Automobile Vehicles - Szodrai, Ferenc; Pálinkás, Sándor; Juhász, György (International Journal of Engineering and Management Sciences, 2020)
Vehicle-energetic-models are used to analyze the performances and when a comprehensive structure is established even optimization could be done. For these kinds of models, the losses of the vehicles have to be known. These losses could significantly effect of the vehicle fuel consumption. From these losses the rolling resistance, drive elements and aerodynamic drag are discussed. This paper reviews some of the literatures that describes the calculation methods and gives us some idea about the degree of their value. Our further goals are to have an UpToDate loss coefficient dataset and calculation methods for further vehicle-energetic modelling.